Association of Hantavirus Infections and Leptospirosis With the Occurrence of Chronic Kidney Disease of Uncertain Etiology in the North Central Province of Sri Lanka: A Prospective Study With Patients and Healthy Persons - Sunil-Chandra, N. P.; Jayaweera, J. A. A. S.; Kumbukgolla, W.; Jayasundara, M. V. M. L. (Frontiers in Cellular and Infection Microbiology, 2020)
Association of hantavirus infections and leptospirosis with the occurrence of chronic kidney disease of uncertain etiology in the North Central Province of Sri Lanka: A prospective study with patients and healthy persons N.P. Sunil-Chandra1*, J.A.A.S. Jayaweera2, W. Kumbukgolla2, M.V.M.L. Jayasundara1 1. Department of Medical Microbiology, Faculty of Medicine, University of Kelaniya, Sri Lanka 2. Faculty of Medicine & Allied Sciences, Rajarata University of Sri Lanka Correspondence: N.P. Sunil-Chandra sunilchandra@kln.ac.lk Abstract Chronic Kidney disease of uncertain etiology (CKDu) has become a significant disease burden, affecting farming community of Sri Lanka and the exact etiology, which could be multifactorial, is not hitherto established. This study is aimed to determine the association of past hantavirus infection and leptospirosis with the occurrence of CKDu. A cohort (n=179) of known CKDu patients living in high-CKDu prevalent areas of Anuradhapura district of Sri Lanka was compared with a group of 49 healthy, sex-matched younger blood relatives of CKDu patients (control-1) and another 48 healthy, age and sex-matched individuals living in low-CKDu prevalent area (control-2) of the same district where same life style and climate conditions prevail. Fifty out of 179 (27.9%) CKDu patients, 16/49 (32.7%) of control-1 and 7/48 (14.6%) of control-2 were found positive for IgG antibodies to Puumala, Hantaan or both strains of hantaviruses. Hantaan strain specificity was found to be predominant in all study groups. Hantavirus IgG sero-prevalence of healthy individuals living in low-CKDu prevalent area was significantly lower compared to CKDu patients and healthy blood relatives living in high-CKDu prevalent areas (p=0.03). Past hantavirus infection possesses a significant risk for the occurrence of CKDu (OR =4.5; 95% CI-3.1-5.4, p=0.02). In contrast, IgG seroprevalence to hantaviruses was not significantly different in CKDu patients and healthy blood relatives living in high-CKDu prevalent areas indicating past hantavirus infection has no association with the occurrence of CKDu or possibly, healthy blood relatives may develop CKDu in subsequent years. Seroprevalence to leptospirosis showed no significant difference between CKDu patients and healthy controls. Past hantavirus infection in high-CKDu prevalent areas was significantly associated with the occurrence of CKDu with potential risk of developing of CKDu in young individuals.